Well-Posedness of the Right-Hand Side Identification Problem for a Parabolic Equation - Ashyralyev, A.; Erdogan, A. S. (Ukrains’kyi Matematychnyi Zhurnal, 2014)
We study the inverse problem of reconstruction of the right-hand side of a parabolic equation with nonlocal conditions. The well-posedness of this problem in Hölder spaces is established.